2022
DOI: 10.2147/clep.s372341
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Effects on Hospitalizations Due to Mood and Psychotic Disorders: A Nationwide 31-Year Register Study

Abstract: Purpose To examine seasonal patterns of hospital admissions due to mood and psychotic disorders and to investigate whether the admission rates show variation according to the seasonal daylength (photoperiods). Patients and Methods A retrospective nationwide register-based cohort of all psychiatric admissions (N=978,079) during 1987–2017 in Finland was utilized. The smoothed time-series of adjusted ratio of observed and expected (O/E) daily counts were estimated to exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 44 publications
3
10
0
Order By: Relevance
“…Along with the rapidly increasing photoperiod, we found a peak in the overall diagnosis of unipolar depression in April. This overall finding of a spring peak is in line with the results of previous studies of hospital admissions (Dominiak et al, 2015;Fellinger et al, 2022;T ö rmälehto et al, 2022) and suicides (Yu et al, 2020). The explanation for this paradox may be that the abruptly and rapidly increasing light exposure after the cloudy and dark period of the year, especially at northern latitudes, acts as a trigger for depressive feelings, which deepen among those who are already depressed (Partonen et al, 2004), whereas longer-term exposure to light during the summer enhances mood in general (Papadopoulos et al, 2005;Vyssoki et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Along with the rapidly increasing photoperiod, we found a peak in the overall diagnosis of unipolar depression in April. This overall finding of a spring peak is in line with the results of previous studies of hospital admissions (Dominiak et al, 2015;Fellinger et al, 2022;T ö rmälehto et al, 2022) and suicides (Yu et al, 2020). The explanation for this paradox may be that the abruptly and rapidly increasing light exposure after the cloudy and dark period of the year, especially at northern latitudes, acts as a trigger for depressive feelings, which deepen among those who are already depressed (Partonen et al, 2004), whereas longer-term exposure to light during the summer enhances mood in general (Papadopoulos et al, 2005;Vyssoki et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…We observed lower absence rates than expected after the summer solstice, which continued from July to September. These findings corroborate previous research findings that have shown that clinically defined depressive disorders (Overland et al, 2019;Patten et al, 2017), hospital admission due to depressive disorders (Dominiak et al, 2015;Fellinger et al, 2022;T ö rmälehto et al, 2022) and initiation of antidepressant medication (Gardardsdottir et al, 2010) follow a seasonal pattern. However, according to a review, several studies have also failed to show such seasonal patterns (Overland et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations